A stochastic model to estimate the expected time to seroconversion – threshold as sum of two components - R. Sathiyamoorthi, R.M. Palanivel, P. Pandiyan (Recent Research in Science and Technology, 2009)
The spread of the HIV infection has created an pandemic situation all over the world. It has become necessary to have the combined efforts of medical personnel, social workers and mathematicians and statisticians to study the different aspects of this infection and its spread. One of the interesting aspects of study is to estimate the likely time at which an infected person becomes seropositive. It is in this connection the antigenic diversity threshold is considered. The antigenic diversity threshold is a particular level of the antigenic diversity of the invading antigen beyond which the human immune system breaks down and a person becomes seropositive. In this paper the expected time to seroconversion is derived under the assumption that the antigenic diversity threshold comprises of two components namely the natural antigenic diversity threshold level of human immune system and the threshold component due to use of ART. Numerical illustration is also provided.